2011
DOI: 10.1144/0016-76492010-096
|View full text |Cite
|
Sign up to set email alerts
|

Provenance and exhumation of an exotic eclogite-bearing nappe in the Caledonides: a U–Pb and Rb–Sr study of the Jæren nappe, SW Norway

Abstract: The provenance and exhumation history of paragneisses that enclose the 471-458 Ma eclogites in the Caledonian Jaeren nappe, SW Norway, were constrained by performing U-Pb analysis on detrital zircon and Rb-Sr dating of mica. Zircon grains from four samples were analysed by laser ablation inductively coupled plasma mass spectrometry, providing detrital U-Pb ages between 3130 and 620 Ma. These data suggest Laurentian provenance, implying the existence of an early Caledonian (Taconian) HP fragment of Laurentian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 151 publications
2
12
0
Order By: Relevance
“…Early to Middle Ordovician fossils of Laurentian affinity in the Støren nappe (Reed, 1932;Pedersen et al, 1992) and Archean to Paleoproterozoic inherited zircons in Early to Middle Ordovician granitoids intruding the Karmøy ophiolite (Pedersen and Dunning, 1997) suggest that this intraoceanic arc was close to Laurentia, at least by the Early Ordovician. The apparent termination of intraoceanic subduction in the late Early to early Middle Ordovician was coincident with HP metamorphism in the Jaeren nappe (Smit et al, 2011) and widespread mid-to-Late Ordovician deformation in the Köli and Lyngen nappes (Slagstad et al, 2013;Corfu et al, 2014), possibly signifying collision of the intraoceanic arc with Laurentia at that time. Such a scenario could also explain the Early Ordovician HP complexes presently preserved in western Svalbard, as well as the timing of subduction initiation beneath northeast Greenland-Svalbard in the Middle Ordovician.…”
Section: Northwest Baltica (Western Scandinavia)mentioning
confidence: 94%
“…Early to Middle Ordovician fossils of Laurentian affinity in the Støren nappe (Reed, 1932;Pedersen et al, 1992) and Archean to Paleoproterozoic inherited zircons in Early to Middle Ordovician granitoids intruding the Karmøy ophiolite (Pedersen and Dunning, 1997) suggest that this intraoceanic arc was close to Laurentia, at least by the Early Ordovician. The apparent termination of intraoceanic subduction in the late Early to early Middle Ordovician was coincident with HP metamorphism in the Jaeren nappe (Smit et al, 2011) and widespread mid-to-Late Ordovician deformation in the Köli and Lyngen nappes (Slagstad et al, 2013;Corfu et al, 2014), possibly signifying collision of the intraoceanic arc with Laurentia at that time. Such a scenario could also explain the Early Ordovician HP complexes presently preserved in western Svalbard, as well as the timing of subduction initiation beneath northeast Greenland-Svalbard in the Middle Ordovician.…”
Section: Northwest Baltica (Western Scandinavia)mentioning
confidence: 94%
“…from syn-rift sedimentary rocks occurring as xenoliths in the KIC. Detrital zircons from other late Neoproterozoic sedimentary rocks deposited in Iapetus-related rift basins along the margin of Baltica have yielded ages as young as 600 Ma (Bingen et al, 2005;Smit et al, 2011;Lamminen et al, 2015). Thus, even zircons with ages around 600 Ma may be inherited, and represent an earlier phase of rift-related magmatic activity.…”
Section: Age Of the Kicmentioning
confidence: 99%
“…Some of the structurally higher tectonic units of the Køli Nappe Complex host a Laurentian fauna (Bergström 1979;Bruton & Bockelie 1979Spjeldnaes 1985;Bruton & Harper 1988), testifying to the far-travelled origin of these units with respect to Baltica. Recent studies have indicated that terranes within the Seve Nappe Complex are of exotic or Laurentian origin (Root & Corfu 2011;Smit et al 2011). Similarly, it has been suggested that the Kalak Nappe Complex in northernmost Norway, previously thought to be part of the Baltica-derived Middle Allochthon, is exotic with respect to Baltica and should be incorporated in the Upper Allochthon (e.g.…”
Section: Geological Settingmentioning
confidence: 99%